Ekspresi Seni Lukis Karya Affandi Dan Seni Tari Karya Sardono W. Kusumo - Kusmadi Kusmadi (Institut Seni Indonesia Surakarta, 2004)
Expression is a process or result of someone’s or a group of people’s activity in expressing desires, in reacting on the existing reality or wants by using a medium.Basically expresison is a symbol of communication with other people as a symbol has meaning and values. In addition to this, expression contains something thought, felt, hope or dreamt of by the artist as thecreator.From the aest hetic point of view, expression is closely related to art whether It is dance, teat hre, music, painting, craft, graphic art and so on. Expression, besides it can be viewed from the visual aspect, is deeper when viewed from the background of sit so that we can see the spirit of the expression.Keyword: Exspression